2018
DOI: 10.3847/1538-4357/aab498
|View full text |Cite
|
Sign up to set email alerts
|

The Stellar Populations of Two Ultra-diffuse Galaxies from Optical and Near-infrared Photometry

Abstract: We present observational constraints on the stellar populations of two ultra-diffuse galaxies (UDGs) using optical through near-infrared (NIR) spectral energy distribution (SED) fitting. Our analysis is enabled by new Spitzer-IRAC 3.6 µm and 4.5 µm imaging, archival optical imaging, and the prospector fully Bayesian SED fitting framework. Our sample contains one field UDG (DGSAT I), one Virgo cluster UDG (VCC 1287), and one Virgo cluster dwarf elliptical for comparison (VCC 1122). We find that the optical-NIR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 100 publications
12
62
0
Order By: Relevance
“…In Figure 8 we compare the luminosityweighted age distribution of galaxies in our sample to that of UDGs observed in the Coma (Gu et al 2018;Ruiz-Lara et al 2018;Ferré-Mateu et al 2018) and Virgo (Pandya et al 2018) clus- Considering that we only have luminosityweighted ages, the results from the our analysis are expected to be biased toward the youngest populations within a galaxy. Therefore, a few different, non-exclusive scenarios can explain the additional fraction of UDGs with young ages.…”
Section: The Luminosity-weighted Ages Of Field Udgsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 8 we compare the luminosityweighted age distribution of galaxies in our sample to that of UDGs observed in the Coma (Gu et al 2018;Ruiz-Lara et al 2018;Ferré-Mateu et al 2018) and Virgo (Pandya et al 2018) clus- Considering that we only have luminosityweighted ages, the results from the our analysis are expected to be biased toward the youngest populations within a galaxy. Therefore, a few different, non-exclusive scenarios can explain the additional fraction of UDGs with young ages.…”
Section: The Luminosity-weighted Ages Of Field Udgsmentioning
confidence: 99%
“…Comparison of the luminosity-weighted ages of our UDGs, which are primarily in the field, and those of UDGs in the literature(Pandya et al 2018;Gu et al 2018;Ruiz-Lara et al 2018;Ferré- Mateu et al 2018), which are primarily in clusters.…”
mentioning
confidence: 99%
“…These Ultra Diffuse Galaxies (UDGs) appear to be ubiquitous in groups and clusters (e.g., van Dokkum et al 2015a,b;Janowiecki et al 2015;Koda et al 2015;Muñoz et al 2015;Mihos et al 2015Mihos et al , 2017Merritt et al 2016;van der Burg et al 2016;Yagi et al 2016;Janssens et al 2017;Shi et al 2017) but are also observed in the field (e.g., Román & Trujillo 2017;Leisman et al 2017). Spectroscopic studies of a few cases indicate intermediate to old, metal poor stellar populations for UDGs in groups and clusters (Ferré-Mateu et al 2018;Gu et al 2018;Ruiz-Lara et al 2018) while the spectral energy distribution (SED) fitting of a field UDG points towards younger stellar populations in the field (Pandya et al 2018). Possible formation scenarii include UDGs being (i) failed Milky Way-like galaxies that lost their gas after forming their first stars (van Dokkum et al 2015a(van Dokkum et al ,b, 2016Yozin & Bekki 2015;Peng & Lim 2016;Lim et al 2018), possibly due to the denser environment in groups and clusters, (ii) the highspin tail of the dwarf galaxy population (Amorisco & Loeb 2016;Rong et al 2017;Shi et al 2017), (iii) tidal debris from mergers or tidally disrupted dwarfs (Beasley & Trujillo 2016;Greco et al 2018;Jiang et al 2018) or (iv) galaxies whose spatial extend is due to episodes of inflows and outflows from stellar feedback (Di Cintio et al 2017).…”
Section: Ultra Diffuse Galaxiesmentioning
confidence: 99%
“…Although the abundance of globular clusters in UDGs compared to dwarf galaxies of similar masses displays a significant scatter, its often large value may indi-cate intense star formation episodes in the past Peng & Lim 2016;van Dokkum et al 2016van Dokkum et al , 2017Lim et al 2018;Amorisco et al 2018). Some UDGs also seem to harbour signs of recent or ongoing star formation (Martínez-Delgado et al 2016;Trujillo et al 2017;Shi et al 2017;Pandya et al 2018) while both Janowiecki et al (2015) and Shi et al (2017) report group UDGs rich in atomic HI gas. Martín-Navarro et al (2019) further interpret the high [Mg/Fe] abundance ratio of a field UDG with an extended star formation history as a possible result of supernova-driven gas outflows.…”
Section: Ultra Diffuse Galaxiesmentioning
confidence: 99%
“…Lim et al 2018;Amorisco et al 2018), and their stellar populations tend to be old and metal-poor (e.g. Kadowaki et al 2017;Ferré-Mateu et al 2018;Gu et al 2018;Pandya et al 2018;Ruiz-Lara et al 2018). Furthermore, unlike typical dwarfs, UDGs tend to be absent in the centre of clusters (e.g.…”
Section: Introductionmentioning
confidence: 99%